152k views
1 vote
I need to multi-step function inverse, photo will be included

I need to multi-step function inverse, photo will be included-example-1
User JamesW
by
4.9k points

1 Answer

8 votes

Answer:

inverse:
f^(-1)(x) = \sqrt[5]{x^3 - 5}

Step-by-step explanation:

Given: f(x) =
(x^5 +5)^{(1)/(3) }

let f(x) be y

y =
(x^5 +5)^{(1)/(3) }

To find inverse, make x the subject.


y^3 = x^5 + 5


y^3 - 5 = x^5


x = \sqrt[5]{y^3 - 5}

change signs:


f^(-1)(x) = \sqrt[5]{x^3 - 5}

User Jack AKA Karthik
by
5.4k points